Production of Talk Show Program â€œBreakoutâ€ and â€œKimchiâ€ at PRO 2 RRI Semarang (Creative Director) - Margaret, Liza; Ratri Rahmiaji, M.Si, Dr. Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The Radio of Republic Indonesia (Radio Republik Indonesia - RRI) is the oldest and the only governmentâ€™s radio which has visions to embody Indonesia public broadcasting as the extensive network radio, character development of nation, and as the world class radio. RRI has a very extensive network, from Aceh to Papua, but not many young people are interested listening to the RRI. The basic reasons of that case are the RRI image as radio news and radio for the older. Solution to overcome the matter is creating talk show programs like â€œBreakoutâ€ and â€œKimchiâ€ in PRO 2 RRI Semarang. Those programs are addressed to young people as the listener target. Thus, the paramount expectation by creating those programs is to increase the listener of RRI PRO 2 Semarang, in particular the young people. During the execution of those programs, the author acts as creative director who has the responsibility to make the programs more interesting by making earcatcher, voxpop, quiz and poster in supporting the process of buzzing in media social. Result of the post-production questionnaire shows that through the production of